2003
DOI: 10.1088/0957-4484/14/7/323
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular synthesis of gold nanoparticles by a novel alkalotolerant actinomycete,Rhodococcusspecies

Abstract: The development of reliable, eco-friendly processes for the synthesis of nanoscale materials is an important aspect of nanotechnology. In this paper, we report on the use of an alkalotolerant actinomycete (Rhodococcus sp.) in the intracellular synthesis of gold nanoparticles of the dimension 5-15 nm. Electron microscopy analysis of thin sections of the gold actinomycete cells indicated that gold particles with good monodispersity were formed on the cell wall as well as on the cytospasmic membrane. The particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
235
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(263 citation statements)
references
References 36 publications
(45 reference statements)
8
235
0
2
Order By: Relevance
“…The ability of bacteria, fungi, actinomycetes (19), yeast (20), algae (21) and plants (22) to accumulate gold ions from solution has been reported and the synthesis of gold nanoparticles has been successfully demonstrated in a range of organisms including Bacillus sp. (23), fungal species such as Verticillium and Fusarium (24,25), actinomycete such as Rhodococcus (26) and Thermomonospora (27) and lactic acid bacteria (28).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of bacteria, fungi, actinomycetes (19), yeast (20), algae (21) and plants (22) to accumulate gold ions from solution has been reported and the synthesis of gold nanoparticles has been successfully demonstrated in a range of organisms including Bacillus sp. (23), fungal species such as Verticillium and Fusarium (24,25), actinomycete such as Rhodococcus (26) and Thermomonospora (27) and lactic acid bacteria (28).…”
Section: Introductionmentioning
confidence: 99%
“…8 The main route to the production of a noble metal colloid is reduction of the metal salt with a suitable reducing agent, usually in the presence of a stabilizer. 9,10 It has, however, been discovered that certain plants 11,12 and bacteria 13,14 are able to produce metal colloids without the need for an external reducing reagent. One such plant is alfalfa, whose seeds efficiently reduce gold and silver salts.…”
Section: Introductionmentioning
confidence: 99%
“…In this present century, Nano-technology became the most recognized technology which revealed its ability to synthesize new products with diverse applications and advantages. Nanoparticles synthesized by biotechnological aid is done with the help of living entities such as bacteria (Farhoodi, 2016;Khalaj et al, 2016;Castro-Mayorga et al, 2016;Couch et al, 2016;Souza and Fernando, 2016;Shahverdi et al, 2007;Dhandapani et al, 2014;Mohite et al, 2015), fungi (Ahmad et al, 2014;Govender et al, 2009), actinomycetes (Manivasagan et al, 2015;Ahmad et al, 2003), algae (Sudha et al, 2013;Govindaraju et al, 2009). It has been reported that micro-.…”
Section: Introductionmentioning
confidence: 99%